Making administrative work visible : data-driven advocacy for understanding the labor of writing program administration - Graziano, Leigh; Halasek, Kay; Hudgins, Remi; Miller-Cochran, Susan K.; Napolitano, Frank M.; Szymanski, Natalie (Utah State University Press, 2023)
"Making Administrative Work Visible brings together graduate students, associated faculty, administrative staff, and tenured and tenure-track faculty at community colleges, regional state universities, liberal arts colleges, private colleges, and research-intensive institutions across the country to speak to the challenges faced by those who do writing program administration work"--